Evaluating aging in cats: How to determine what is healthy and what is disease. Issue 7 (July 2016) - Bellows, Jan; Center, Sharon; Daristotle, Leighann; Estrada, Amara H; Flickinger, Elizabeth A; Horwitz, Debra F; Lascelles, B Duncan X; Lepine, Allan; Perea, Sally; Scherk, Margie; Shoveller, Anna K
Practical relevance: Many of the changes that occur with aging are not considered pathologic and do not negatively affect overall wellness or quality of life. Ruling out disease is essential, however, when attempting to determine whether an aged cat can be considered 'healthy'. A clear understanding of the normal and abnormal changes that are associated with aging in cats can help practitioners make decisions regarding medical management, feeding interventions and additional testing procedures for their aged patients. Clinical challenges: It can be difficult to determine if a cat is displaying changes that are appropriate for age. For example, healthy aged cats may have hematologic or serum biochemistry changes that differ from those of the general feline population. Assessment of behavioral health and cognitive changes, as well as auditory, olfactory and visual changes, can also be challenging in the aged patient. Goals: This is the second of two review articles in a Special Issue devoted to feline healthy aging. The goals of the project culminating in these publications included developing a working definition for healthy aging in feline patients and identifying clinical methods that can be used to accurately classify healthy aged cats. This second review proposes criteria for assessing 'healthy aged cats'. Evidence base: There is a paucity of research in feline aging. The authors draw on expert opinion and available data in both the cat and other species.